Education Policy Reform and Professional Identities: The Case of Secondary Education in Spain - Bolívar, Antonio; Gallego, María Jesús; León, María José; Pérez, Purificación (Education Policy Analysis Archives, 2005)
The article analyses the effects of the large scale educational reform policies on teachers' professional identities, based on a review of the literature and data from a study we carried out. Professional identity crisis is placed within the broader framework of the modernity crisis. The story of this crisis (influences and causes) includes a description of the education reform of the 1990"s (LOGSE, Ley de Ordenación General del Sistema Educativo), the role played by teacher training in aggravating the problem, and the reasons secondary teachers have resisted educational change. In this framework, the different types of identity adopted by teachers faced with this change are studied, and the results of a qualitative study through the voices of the teachers are described. Finally, two exit plans are presented: a political use of nostalgia, employed by the conservative government to gain the support of a large number of teachers; and the exploration of new avenues for the reconstruction of professional identities. The idea is to re-examine alternative arguments about what schools should be in the "second modern society."